2013
DOI: 10.3347/kjp.2013.51.2.177
|View full text |Cite
|
Sign up to set email alerts
|

Dot-Blot Immunoassay of Fasciola gigantica Infection using 27 kDa and Adult Worm Regurge Antigens in Egyptian Patients

Abstract: The purpose of the present study was to evaluate the potential role of the 27-Kilodalton (KDa) antigen versus Fasciola gigantica adult worm regurge antigens in a DOT-Blot assay and to assess this assay as a practical tool for diagnosis fascioliasis in Egyptian patients. Fasciola gigantica antigen of an approximate molecular mass 27-(KDa) was obtained from adult worms by a simple elution SDS-PAGE. A Dot-Blot was developed comparatively to adult worm regurge antigens for the detection of specific antibodies from… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
7
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(9 citation statements)
references
References 19 publications
(23 reference statements)
2
7
0
Order By: Relevance
“…Superiority of Fasciola Ag fractions in the range of (25-32) kDa in accurate diagnosis was proved previously by several authors as Farghaly et al [1] for (23-28 kDa) [23] and [8] for 27 kDa using the EITB technique.…”
Section: Discussionsupporting
confidence: 63%
See 1 more Smart Citation
“…Superiority of Fasciola Ag fractions in the range of (25-32) kDa in accurate diagnosis was proved previously by several authors as Farghaly et al [1] for (23-28 kDa) [23] and [8] for 27 kDa using the EITB technique.…”
Section: Discussionsupporting
confidence: 63%
“…At the same time Kamel et al [8] determined that the most specific protein band in F. hepatica ES Ag is that of 14-38 kDa band and the most specific one is that of 27 kDa.…”
Section: Introductionmentioning
confidence: 98%
“…A number of other studies also detected a 27 kDa protein band as an immunodominant band of both somatic and E/S of Fasciola species (Santiago and Hillyer 1988; Attallah et al, 2002; Dixit et al, 2008; Kamel et al, 2013). However the studies of Sampaio Silva et al, (1996), Hammami et al, (1997) and Rokni et al, (2004), revealed the protein band of 29 kDa molecular weight as the principle band of the E/S antigen of Fasciola species for the serodiagnosis of fasciolosis.…”
Section: Discussionmentioning
confidence: 82%
“…The 27 kDa polypeptide of F . gigantica has been studied by previous investigators in the dot blot immunoassay for the detection of fasciolosis in Egyptian patients [ 60 ]. In another study the 27 kDa has been used for the immunodiagnosis of human fasciolosis [ 61 ].…”
Section: Discussionmentioning
confidence: 99%